Structural change and poverty reduction in Brazil : the impact of the DOHA round - Mauricio (Policy research working paper, 2006)
"Over the medium time horizon, skill upgrading, differentials in sectoral technological progress, and migration of labor out of farming activities are some of the major structural adjustment factors shaping the evolution of an economy and its connected poverty trends. The main focus of the authors is understanding, for the case of Brazil, how a trade shock interacts with these structural forces and ascertaining whether it enhances or hinders medium-term poverty reduction. In particular, they consider the interactions between the migration of labor out of agriculture, a potentially important poverty reduction factor, and trade liberalization, which increases the price incentives to stay in agriculture. A recursive-dynamic computable general equilibrium model simulates Doha scenarios and compares them against a business as usual scenario. The authors estimate the poverty effects using a microsimulation model that primarily takes into account individuals' labor supply decisions. Their analysis shows that trade liberalization does contribute to structural poverty reduction. But unless increased productivity and stronger growth rates are attributed to trade reform, its contribution to medium-term poverty reduction is rather small. "--World Bank web site